Parameters Influencing Reactivity and Regioselectivity in the Methoxycarbonylation of Arylalkenes - du Plessis, Maretha; Marais, Charlene; Bezuidenhoudt, Barend C. B. (Synthesis, 2016)
Previous research showed that the steric bulk, electronic character, and bite angle of the ligand have an influence on both the catalyst activity and regioselectivity of hydroformylation and hydroesterification reactions. However, little is known in this regard about the influence of the steric and electronic environment around the double bond of the substrate. A variety of arylalkenes were therefore subjected to methoxycarbonylation to investigate the steric and electronic effects of substituents on the aromatic ring of the substrate on the regioselectivity and reactivity in the methoxycarbonylation reaction of these substrates with a Pd(II)/Al(OTf)3/Ph3P catalyst system.
Keywords: hydroesterification; arylalkenes; palladium; aluminum triflate; regioselectivity